Project Schedule Evaluation Using Project Manegement Software: A Case Study in an Electric Steam Power Plant in Indonesia. (August 2019) - Miranda, S; Helia, V N
Abstract: Project scheduling plays an important role among knowledge areas according to Project Management Body of Knowledge (PMBOK). There are six constraints to be considered in managing a project: scope, cost, schedule, quality, risk, and human resource. In project scheduling, a schedule baseline must be determined properly in order to meet all deliverables presenting schedule milestones, the activities, and network diagram. Each process within project scheduling management (inputs-tools and technique-outputs) are: (1) plan schedule management; (2) define activities; (3) sequence activities; (4) estimate activity duration; (5) develop schedule; (6) control schedule. According to the data obtained, the shelter at ash disposal was accomplished 19 days behind the target set of 38 days. This condition is evaluated using project scheduling process. One constraint involved are 18 human resources assigned into the project. A new schedule is proposed by interviewing the project sponsor to identify the dependencies among activities and simulated using a project management software called Microsoft Project 2016. It can highlight the critical path as well as leads and lags of all activity. The new schedule result shows that project completion can increase 9 days from 57 days to 48 days.